DESCRIPTION OF ELDERLY KNOWLEDGE ABOUT ELDERLY POSYANDU IN TUMENGGUNG BARU TUMENGGUNGAN VILLAGE, LAMONGAN DISTRICT - Sairozi, Ali; Hariyanto, Rohmad Nur (Journal of Vocational Nursing, 2020)
Introduction: Advanced age is a natural process that cannot be avoided, meaning that aging is a natural rule. The process of aging is caused by biological factors which consist of 3 phases, namely progressive phase, stable phase and regrefif phase. In the anatomic structure the process of aging is seen as a deterioration in the cell. From the initial survey of 25 elderly in Tumenggung, Lamongan Subdistrict, Lamongan Regency, there were problems regarding the decline of Tumenggung elderly Posyandu visits in 2010. The purpose of this study was to identify the description of knowledge about the elderly posyandu in Tumenggung Baru, Lamongan District, Lamongan Regency. Methods: This study used a descriptive design, with a population of 25 people and a sample of 30 people. Sampling used is total sampling. Data collection with questionnaire sheets, data processing techniques used are Coding, Scoring, and Tabulating techniques, Scoring, then adjusted in tabulation and narration.  Results: From the results of the study showed that most (72%) of the elderly had good knowledge about the elderly posyandu and a small percentage (12%) had moderate knowledge and 4 elderly (16%) had moderate knowledge.  Conclusion: The conclusion of the study is that most of the elderly at the Posyandu in the old Tumenggung elderly district of Lamongan are wellinformed, so that health workers can increase the motivation of the elderly.